Aerogels for waterborne pollutants purification - Abdul, Moheman; Showkat, Ahmad Bhawani; Abu, Tariq (Elsevier, 2021)
Waterborne pollutants and associated diseases are a widespread public health issue in the world. These diseases are connected directly to the degradation and contamination of the environment. In recent years, aerogels have drawn the interest of researchers and technologists in the field of water purification because of their ultra-low density, high surface area, higher adsorption power, good mechanical strength, ultra-high porosity, ultra-low thermal conductivity, ultra-low dielectric constant. This chapter includes up-to-date information on the use of aerogels/hybrid aerogels to eliminate waterborne pollutants including metal ions, pathogens, colorants, oil waste, and other toxic compounds. The use of aerogels/hybrid aerogels for microbe removal techniques is surprisingly understudied. Studies revealed that compared with aerogels, hybrid aerogels showed excellent adsorption performance. Unlike metal oxide, graphene, and carbon nanotube-derived aerogels, bio-based aerogels are more cost-effective, safe, and environmentally friendly. Despite the different applications and benefits of aerogels in the purification of waterborne pollutants, some problems related to their use remain unresolved.